Pengaruh Kombinasi Latihan Beban dengan Metode Pyramid set dan Konsumsi Susu Tinggi Protein Terhadap Peningkatan Massa Otot - Melfi Triani Siska; Zahtamal Zahtamal; Fachriani Putri (Fakultas Kedokteran Universitas Riau, 2019)
Weight training with pyramid set method and high protein milk are the effective methods to increase muscle mass. There are not many studies that combined these 2 methods to increase the muscle mass The purpose of this study was to analyze the effect of combination of pyramid weight training sets and consumption of high protein milk to increase the muscle mass. This type of study is a quasi-experimental one group with a pre and post test design. The study period was 8 weeks with 32 meetings and high protein milk in of 32 grams of whey protein concentrate before and after exercise.The results of this study also prove that there is a significant effect of intervention on participants muscle mass with p = 0,000. It can be concluded that the combination of pyramid weight training sets and high protein milk consumption is effective to increasing muscle mass.